Effect of Cyclosporin A on Immediate Early Gene in Rat Global Ischemia and Its Neuroprotection - Tatsuo Yamaguchi; Kazuto Miyata; Futoshi Shibasaki; Atushi Isshiki; Hiroyuki Uchino (Elsevier, 2006)
Abstract.: The expressions of the immediate early genes, c-fos and c-jun, and their product proteins C-FOS, C-JUN, and P-JUN were examined in the hippocampal CA1 subfield after global ischemia and reperfusion in rats treated with cyclosporin A. More than 90% neuronal cell death was seen in hippocampal CA1 7 days after global ischemia in control animals, but only 5% cell death after ischemia was seen in the CsA-treated animals. The expressions of c-fos and c-jun mRNA in the control animals were detected with an increase from 1 to 48 h after ischemia. On the other hand, they showed significant suppression in the CsA-treated animals. Increased expressions of C-FOS were found 1, 24, and 48 h after reperfusion in the control animals. In the CsA-treated animals C-FOS expression was found to increase, but the expression level reduced to a statistically insignificant level within 48 h after the ischemia. C-JUN and P-JUN expressions increased in control animals, but were almost completely suppressed in the CsA-treated animals. The present study demonstrated that the suppressant effects of CsA on IEGs and their products might have causal relationship to the dramatic protecting effect of the drug against delayed neuronal cell death. Keywords:: immediate early gene, ischemia, immunosuppressant, hippocampus, delayed neuronal death